2004
DOI: 10.1093/toxsci/kfh077
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Analysis of Switch-Like Induction of CYP1A1 in Liver Cell Lines

Abstract: The shape of the dose-response curve may vary depending on whether one examines response at a population or a single cell level. Populations of cells may exhibit a graded response whereas single cell responses may have threshold or switch-like behavior. Studies in vivo and in vitro using primary hepatocyte cultures have shown that induction of CYP1A1 in the liver exhibits switch-like behavior in response to PCB 126 (3,3',4,4',5-pentachlorobiphenyl). The goal of the present study was to determine if two liver c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
4
20
0
1
Order By: Relevance
“…These results indicated that CYP1A1 induction was switch-like, and once the threshold was triggered, the induction was graded. Similar results were later reported in H4IIE rat hepatoma cells (Broccardo et al 2004). This phenomenon was described as "a hybrid switching module where a switch works in concert with a rheostat, much like a dimmer on a light in a home" (French et al 2004), or simply as a "dimmer switch" (Wilson 2004).…”
Section: Level 3 Models: a Heterogeneity Of Protein Induction In Thesupporting
confidence: 91%
“…These results indicated that CYP1A1 induction was switch-like, and once the threshold was triggered, the induction was graded. Similar results were later reported in H4IIE rat hepatoma cells (Broccardo et al 2004). This phenomenon was described as "a hybrid switching module where a switch works in concert with a rheostat, much like a dimmer on a light in a home" (French et al 2004), or simply as a "dimmer switch" (Wilson 2004).…”
Section: Level 3 Models: a Heterogeneity Of Protein Induction In Thesupporting
confidence: 91%
“…The model therefore suggested that the dose-response for induction of CYP1A1 and CYP1A2 by TCDD is highly nonlinear at low doses. This Wnding is substantiated by recent data demonstrating a switch-like behavior of CYP1A1 induction in response to PCB-126 when determined on a single cell level in cell lines (Broccardo et al, 2004).…”
Section: Induction Of Cyp1a1/cyp1a2supporting
confidence: 57%
“…Higher concentrations up to 0.005% (w/v) did give a greater degree of induction but led to very high levels of mortality (Wang and Hobbs 1995). The reason might be that the response of the single cell in the population to insecticide is different at various concentrations (Broccardo et al 2004); some induced at lower concentrations may have died at the higher concentration of insecticide; the detoxifying enzymes (P450s) decreased with increasing insecticide concentration, so their ability to detoxify the cells declined, and more cells then died.…”
Section: Discussionmentioning
confidence: 99%